Prioritization of Industrial Activities in Yazd Province with an Emphasis on the Importance of Water Resources: Integrating the Input-Output Model and AHP - Zahra Nasrollahi; Mehran Zarei (فصلنامه پژوهش‌های اقتصادی ایران, 2017)
Water plays a significant role in sustainable development process of every region both as a natural resource and as a production input. Therefore, ignoring water resources limitation in investment priorities in dry regions as Yazd province may lead to non-optimal decisions, which are not in line with sustainable development goals. Hence, the aim of this paper is to prioritize the industrial activities in Yazd province with an approach to sustainable development and with an emphasis on importance of water resources. As a result, the current study has tried to cover various aspects of sustainable development. For this purpose, firstly input-output table for Yazd province was estimated using AFLQ method. Then, industrial sectors of Yazd province were prioritized by integration of input-output model and analytic hierarchy process (AHP), considering five criteria including water use, employment, inter-sectoral linkages, emission and value added. The results show that sector of "electrical equipment and office machinery" has a higher priority for investment than other sectors. Findings also show the importance of water use, so that ignorance of this criterion leads to significantly different prioritization results.